2007
DOI: 10.1055/s-2007-965325
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative and Midterm Outcomes of Minimally Invasive and Endoscopic Great Saphenous Vein Harvesting for Coronary Artery Bypass Grafting - A Prospective Analysis

Abstract: Endoscopic vein harvesting seems to be superior to minimally invasive vein harvesting in terms of a significant reduction of residual leg oedema, pain intensity and particularly saphenous neuropathy in the postoperative and midterm follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A possible explanation is that saphaenous nerve injury can occur as a result of surgical handling or postoperatively from compression caused by subcutaneous suturing. Relevant literature addressed alternative techniques to avoid this injury (Bonde et al., ; Allen et al., ; Simek et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that saphaenous nerve injury can occur as a result of surgical handling or postoperatively from compression caused by subcutaneous suturing. Relevant literature addressed alternative techniques to avoid this injury (Bonde et al., ; Allen et al., ; Simek et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher percentage of complications in the OVH than the EVH group was accounted for by more frequent early lymphatic drainage. Thus, in the EVH group, according to the findings of previous studies, lymphatic drainage was observed in approximately 10–12 % of patients [ 18 ]. However, in the present study, it was only observed in 4.5 % of patients.…”
Section: Discussionmentioning
confidence: 84%
“…Lymphatic discharge was significantly lower among the endoscopic group at seven days post-operation. Also, residual edema was significantly lower both at seven and three months follow-up after endoscopic surgery [39]. Additionally, early rehabilitation to restore lymphatic drainage is another means to prevent lymphedema following saphenous harvesting surgery but unfortunately, his lymphedema was not diagnosed and he was not referred to the specialized center for lymphedema management.…”
Section: From Neglecting Lymphedema To the Patient's Qolmentioning
confidence: 99%